1998
DOI: 10.1002/jor.1100160514
|View full text |Cite
|
Sign up to set email alerts
|

Quadriceps load aggravates and roofplasty mitigates active impingement of anterior cruciate ligament grafts against the intercondylar roof

Abstract: Because of the complications of impingement of anterior cruciate ligament grafts on the intercondylar roof and because current surgical procedures locate the tibial tunnel such that impingement is avoided during passive but not active extension, the objectives of this study were to determine if (a) active extension precipitates and aggravates roof impingement, and (b) a roofplasty mitigates the effects of impingement. The tibial translation, flexion angle defining the onset of roof impingement, graft-roof cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
40
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 26 publications
0
40
0
Order By: Relevance
“…11 While the transtibial technique was widely used to create femoral bone tunnels in the 1990s, the nonanatomic high position (11 o'clock for right knee and 1 o'clock for left knee) was perceived as proper positioning of the femoral bone tunnel because of good isometricity, resulting in an increased incidence of notch impingement. In the context of the high position, the ACL graft is prone to impingement on the superior wall of the notch (ie, roof impingement) with the knee in extension, unless notchplasty is performed concomitantly.…”
mentioning
confidence: 99%
“…11 While the transtibial technique was widely used to create femoral bone tunnels in the 1990s, the nonanatomic high position (11 o'clock for right knee and 1 o'clock for left knee) was perceived as proper positioning of the femoral bone tunnel because of good isometricity, resulting in an increased incidence of notch impingement. In the context of the high position, the ACL graft is prone to impingement on the superior wall of the notch (ie, roof impingement) with the knee in extension, unless notchplasty is performed concomitantly.…”
mentioning
confidence: 99%
“…Descriptive anatomic studies have concluded that the intercondylar notch volume is correlated with ACL volume; thus, a smaller intercondylar notch would correspond to a smaller, weaker ACL [3,4]. On the other hand, proponents of notchplasty, or removal of part of the intercondylar notch to widen the aperture, suggest that a normal-sized ACL is housed in a small intercondylar notch, which creates wear of the native ACL or graft on the lateral femoral condyle during extension and internal rotation movements [7][8][9]18]. More recent studies by Iriuchishima et al [16] on human cadaveric knees and in post-operative imaging analyses [14,15] have determined that if the graft is placed anatomically, whether using single-or double-bundle reconstruction techniques, the resultant knee has more biomechanical instability in a virtually impingement-free environment.…”
Section: Discussionmentioning
confidence: 99%
“…Grafts are more uniform in sagittal width from origin to insertion (8-10 mm), and cannot replicate the broad insertion of the intact ACL. 3,12 Therefore, placing the tibial tunnel anteromedially in the broad insertion of the intact ACL places the graft too anterior and causes roof impingement [1][2][3][4]13 There is wide variability in roof angle and knee extension between patients that can be accounted for by customizing the placement of the tibial tunnel in the sagittal plane. Roof…”
Section: Rationale For Preventing Extension and Flexion Lossmentioning
confidence: 99%
“…When the entire tibial tunnel is placed anterior to the intercondylar roof, the impingement is more severe, resulting in abrasion and stretchout of the graft and recurrent anterior instability. [1][2][3][4] Therefore, the prevention of extension loss and maintenance of anterior laxity requires proper placement of the tibial tunnel in the sagittal plane.…”
mentioning
confidence: 99%